Everyday Cosmopolitanism in Representations of Europe among Young Romanians in Britain. (April 2019) - Andreouli, Eleni; Howarth, Caroline
The article presents an analysis of everyday cosmopolitanism in constructions of Europe among young Romanian nationals living in Britain. Adopting a social representations approach, cosmopolitanism is understood as a cultural symbolic resource that is part of everyday knowledge. Through a discursively oriented analysis of focus group data, we explore the ways in which notions of cosmopolitanism intersect with images of Europeanness in the accounts of participants. We show that, for our participants, representations of Europe are anchored in an Orientalist schema of West-vs.-East, whereby the West is seen as epitomising European values of modernity and progress, while the East is seen as backward and traditional. Our findings further show that representations of cosmopolitanism reinforce this East/West dichotomy, within a discourse of 'Occidental cosmopolitanism'. The article concludes with a critical discussion of the diverse and complex ideological foundations of these constructions of European cosmopolitanism and their implications.